Vertical equity of healthcare in Taiwan: health services were distributed according to need - Wang Shiow-Ing; Yaung Chih-Liang (BMC, 2013)
Abstract Introduction To test the hypothesis that the distribution of healthcare services is according to health need can be achieved under a rather open access system. Methods The 2001 National Health Interview Survey of Taiwan and National Health Insurance claims data were linked in the study. Health need was defined by self-perceived health status. We used Concentration index to measure need-related inequality in healthcare utilization and expenditure. Results People with greater health need received more healthcare services, indicating a pro-need character of healthcare distribution, conforming to the meaning of vertical equity. For outpatient service, subjects with the highest health need had higher proportion of ever use in a year than those who had the least health need and consumed more outpatient visits and expenditures per person per year. Similar patterns were observed for emergency services and hospitalization. The concentration indices of utilization for outpatient, emergency services, and hospitalization suggest that the distribution of utilization was related to health need, whereas the preventive service was less related to need. Conclusions The universal coverage plus healthcare networking system makes it possible for healthcare to be utilized according to need. Taiwan's experience can serve as a reference for health reform.